Effects of wisdom and religiosity on subjective well-being in old age and young adulthood: exploring the pathways through mastery and purpose in life. (20th November 2018) - Ardelt, Monika; Ferrari, Michel
ABSTRACT: Objectives: Prior research found that the positive association between wisdom and subjective well-being might at least partially be explained by a greater sense of mastery and purpose in life. This study tested whether religiosity provides an alternative pathway to well-being and whether the associations are moderated by age cohort and nation of residency. Design and Participants: A quota sample design was used, stratified by age group, sex, and nation of residency, to collect cross-sectional survey data of 111 older adults (age range 62–99 years, M = 77.20, SD = 8.98) and 100 young adults (age range 21–30 years, M = 24.05, SD = 2.69) from Canada and the United States. Measurements: Face-to-face interviews were conducted to administer the survey. All measures consisted of validated scales and items. Results: Multi-group path analysis confirmed that mastery and purpose in life partially mediated the association between wisdom and well-being. Religiosity offered an alternative pathway to well-being, also partially through a greater sense of mastery and purpose in life. Wisdom was statistically more strongly related to mastery among older adults, whereas the association between mastery and purpose in life was statistically stronger among young adults. The mediated pathways from wisdom and religiosity to well-being did not differ by nation of residency. Conclusions: These results highlight the importance of internal strengths for subjective well-being among both young and older adults and add confidence to the generalizability of the mediated path model for North America.